2020
DOI: 10.1016/j.ijcha.2020.100631
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated atrial fibrillation: Incidence, putative mechanisms and potential clinical implications

Abstract: Coronavirus disease 2019 (COVID-19) is a novel, highly transmittable and severe strain disease, which has rapidly spread worldwide. Despite epidemiological evidence linking COVID-19 with cardiovascular diseases, little is known about whether and how COVID-19 influences atrial fibrillation (AF), the most prevalent arrhythmia in clinical practice. Here, we review the available evidence for prevalence and incidence of AF in patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 93 publications
6
142
0
15
Order By: Relevance
“…A limited number of studies revealed that COVID-19 patients with AF were older and most of them had at least one preexisting risk factor, including hypertension, CAD, CHF, renal disease, prior stroke or pulmonary disease [ 18 , 20 , 27 ], while some did not report any illness [ 28 ]. COVID-19 patients with comorbid diseases, such as CHF, hypertension, CAD, DM and RF, have an extremely poor prognosis, compared with subjects without co-morbidities [ 13 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies revealed that COVID-19 patients with AF were older and most of them had at least one preexisting risk factor, including hypertension, CAD, CHF, renal disease, prior stroke or pulmonary disease [ 18 , 20 , 27 ], while some did not report any illness [ 28 ]. COVID-19 patients with comorbid diseases, such as CHF, hypertension, CAD, DM and RF, have an extremely poor prognosis, compared with subjects without co-morbidities [ 13 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other contributing factors (which may cause ventricular arrhythmias as well) include immune-mediated injury caused by inflammatory cytokines, which can prolong the action-potential duration by interacting with potassium and calcium channels, and myocardial ischemia due to virus-mediated vasculitis, viral myocarditis, or underlying coronary atherosclerosis. 7 Ventricular arrhythmias can be mediated by all of the above, but the “off-label” use of some agents with known arrhythmic potential is of particular concern, especially in the absence of any proven benefit. Chief among these medications are hydroxychloroquine, chloroquine, and azithromycin, all of which prolong the QT interval by interacting with the hERG potassium channel and can precipitate torsades de pointes when used individually or in combination.…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
“…However, the use of therapeutic anticoagulation may occur as a result of many reported complications of COVID-19 including venous thromboembolism, arterial thromboembolism, cardiac arrhythmia, and disseminated intravascular coagulation. [51][52][53][54][55][56][57][58] We surmised that an intensification of anticoagulation indicated an adverse change in clinical condition. Third, this study was conducted on Veterans currently receiving care in the VA, who are older and have a higher prevalence of chronic health conditions and risk behaviors than the general US population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%